Narrativ identitet: En studie kring studenters narrativa identitet i relation till studentengagemang - Bojestig,Anna; Lundberg Winding,Nikolai (2026)
This essay examined the relationship between narrative identity and student engagement, in addition to the associations with extraversion, openness, autobiographical recollection, and sense of belonging. The theoretical framework was based on the Five-Factor model, specifically extraversion and openness, alongside sense of belonging, narrative identity, and autobiographical-recollection. Previous research provided some support for connections between these variables; however, their interrelations and the current context remained limited. The study examined three hypotheses concerning correlations among the variables. The method consisted of a quantitative questionnaire, including demographic questions, and the scales, the brief ART, sense of belonging, awareness of narrative identity, extraversion and openness. The sample comprised current and former students in Lund who were or had been actively involved in any student engagement. The results demonstrated significant correlations between ART-narrative identity, sense of belonging-narrative identity and sense of belonging-extraversion. No significant correlations were found between student engagement-narrative identity and openness-sense of belonging. Therefore, the first hypothesis could neither be confirmed nor denied due to non-significant results, missing data and variable construction issues, whilst partial support was identified for the second and third hypotheses. The findings were impacted by a low response frequency, an underexplored population, missing data and adapted measuring instruments, which may impact the validity and generalisability. Future research could advantageously include a bigger sample and focus on neighbouring dimensions. Collectively, the results indicate that the university can benefit from promoting a sense of belonging, as participation in student engagements may contribute to the development of the narrative identity.
Keywords: Narrativ Identitet; Autobiografiskt Tänkande; Social Tillhörighet; Studentengagemang; Femfaktormodellen; Narrative Identity; Autobiographical Reasoning; Sense of Belonging; Student Engagements; Big Five